The Impact of Oil Refinery Market Power on Retail Fuel Prices in the European Union - Zirgulis, Aras; Petručionis, Liutauras; Huettinger, Maik (Ekonomika, 2017)
The present study investigates the degree to which imperfect competition in the oil sector affects end retail prices. Specifically, we test how positive and negative price shocks in the oil market translate to final retail prices for petrol, diesel, and heating oil prices, focusing on the asymmetry of the price changes. We assume that the higher the level of imperfect competition, the more asymmetric the price change between the initial oil and final retail products will be. In addition, we also test the degree to which uncertainty, or oil price volatility, affects the final prices for these same products. We find that our proxy for market power does affect retail price asymmetries and that increasing volatility lowers retail price asymmetries.
Keywords: Imperfect Competition; Oil industry; Retail fuel price; Price asymmetry; Petrol; Heating oil; Diesel